The Deceitfulness of Sticky Costs on Banking Systems - César Vela-Beltrán-del-Río; Luis Felipe Llanos Reynoso (STIE Malangkucecwara, 2018)
Understanding the true, sometimes deceitful, nature of sticky costs is vital to take advantage of market opportunities and to compete; by aligning the needed substructure to the medium and long term business expectations. Doing so will allow management to be better positioned to achieve such goals. This long-term research (16 years), performed in Mexico, offers a holistic understanding of the real sticky costs behavior in both bullish and bearish markets. The stickiness nature of costs is an unintended manifestation of the embedded conditions of the assets cquired, while pursuing longer term objectives. This is the case because it is through assets, in general, that businesses compete. We will document that costs behave differently in bearish and bullish markets; costs, under general market conditions, perform at different rates in each market. We introduced a dummy regression variable to determine if the increase in administrative spending is positively related to an income increase, considering years with income increases and decreases. We also found that costs will continue rising, at a lower rate, even in bearish markets, unless there is a global crisis. Those who not understand the actual sticky nature of costs will face their deceitful nature, especially during bearish markets.